2017
DOI: 10.3892/etm.2017.5440
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age, not transient hyperthyrotropinemia impacts brain white matter diffusion tensor imaging in premature infants

Abstract: Abstract. Transient hypothyroidism is common in premature infants and increases the risk of adverse neurodevelopmental outcomes. Thyroid hormone (TH) is involved in oligodendrocyte development and myelination, however, whether transient hypothyroidism is associated with oligodendrocyte dysplasia and abnormal myelination is unclear. The aim of the present study was to investigate correlations among TH levels, neurodevelopmental outcomes and white matter (WM) microstructure in premature infants. The authors desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Therefore, despite its transient nature and the epiphenomenon of severe illness, hypothyroxinaemia in ELBWIs could be a risk factor by itself for both acute mortality and morbidities 10 and later neurodevelopmental deficits in ELBWIs 2426 . However, a recent study reported that GA, but not THOP, played a key role in neuromotor dysfunction in preterm babies 27 . Moreover, thyroid hormone treatment did not attenuate the severity of RDS 28,29 , reduce mortality up to the point of discharge 29 , or improve long-term neurodevelopmental outcome 28,29 .…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, despite its transient nature and the epiphenomenon of severe illness, hypothyroxinaemia in ELBWIs could be a risk factor by itself for both acute mortality and morbidities 10 and later neurodevelopmental deficits in ELBWIs 2426 . However, a recent study reported that GA, but not THOP, played a key role in neuromotor dysfunction in preterm babies 27 . Moreover, thyroid hormone treatment did not attenuate the severity of RDS 28,29 , reduce mortality up to the point of discharge 29 , or improve long-term neurodevelopmental outcome 28,29 .…”
Section: Discussionmentioning
confidence: 95%